Evaluation of CD34+ - and Lin- -selected cells from peripheral blood stem cell grafts of patients with lymphoma during differentiation in culture ex vivo using a cDNA microarray technique - Krontorád Koutná, Irena; Klabusay, Martin; Kohutova, Viera; Krontorád, Petr; Svoboda, Zbyněk; Kozubek, Michal; Mayer, Jiří (Experimental hematology, 2006)
OBJECTIVE: Hematopoietic stem cells (enriched in fraction of CD34+ cells) have the ability to regenerate hematopoiesis in all of its lineages, and this potential is clinically used in transplanting bone marrow or peripheral blood stem cells. Our objective was to assemble a suitable method for evaluating gene expression in enriched populations of hematopoietic stem cells. We compared biologic properties of cells cultured ex vivo obtained using two different ways of immunomagnetic separation (positive selection of CD34+ cells and negative selection of Lin- cells) by means of a cDNA microarray technique. METHODS: CD34+ and Lin- cells were enriched from peripheral blood stem cell (PBSCs) grafts of patients with non-Hodgkin's lymphoma. Isolated cells were in the presence of cytokine PBSCs, Flt-3 ligand, interleukin-3, interleukin-6, and granulocyte colony-stimulating factor. At days 0, 4, 6, 8, 10, 12, and 14 cells were harvested and analyzed by cDNA microarrays. Total cell expansion, CD34+, colony-forming unit for granulocyte-macrophage and megakaryocytes expansion, vitality, and phenotype of cells were also analyzed. RESULTS: cDNA microarray analysis of cultured hematopoietic cells proved equivalence of the two enrichment methods for PBSC samples and helped us characterize differentiating cells cultured ex vivo. CONCLUSION: Our methodologic approach is helpful in characterizing cultured hematopoietic cells cultured ex vivo, but it is also suitable for more general purposes. Equivalence of CD34+ and Lin- selection methods from PBSC samples proved by cDNA microarray may have an implication for graft manipulation in an experimental setting of hematopoietic transplantation. Total cell expansion and colony formation and phenotype from CD34+ selected and from Lin- samples were comparable.
Keywords: imunofenotypizace; Oligonucleotide Array Sequence Analysis; lidé; Financing, Organized; Antigens, CD34; antigeny CD34; financování organizované; Humans; lymfom; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; imunomagnetická separace; DNA, Complementary; Immunophenotyping; transplantace kmenových buněk; Stem Cell Transplantation; Immunomagnetic Separation; Lymphoma; komplementární DNA